Sufi Values as a Framework for Addressing Moral and Spiritual Crises in Contemporary Education - Andri Kurniwan; Rafianas Zuhroh; Wildan Yudistira; Fais El Farisi; Ismali Mubarok (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2026)
This study is motivated by the increasing challenges in modern education, including character degradation, future anxiety, achievement pressure, and the dominance of intellectual-oriented learning that often neglects spiritual development. This study aims to analyze the development of Sufi thought within the Islamic tradition, its transformation into an educational framework, and its contribution to addressing contemporary educational challenges. This research employed a qualitative approach using a systematic literature review method. Data were obtained from 28 selected articles published between 2018 and 2026 through academic databases, including Google Scholar, and DOAJ. The literature was analyzed using qualitative content analysis to identify patterns related to Sufi values, Islamic education, and character formation. The findings reveal that Sufi thought has developed from individual spiritual practices into a holistic educational paradigm integrating intellectual, moral, and spiritual dimensions. Values such as sincerity, patience, tawakkul, and qana’ah contribute to strengthening students’ character, emotional stability, and spiritual resilience. This study contributes theoretically by positioning Sufism as an educational framework and practically by recommending the integration of Sufi values into character-based educational practices.